2021
DOI: 10.3390/ijms22168820
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Comorbidities in Vitiligo: A Brief Review and Report of New Data from a Single-Center Experience

Abstract: Among disorders of pigmentation, vitiligo is the most common, with an estimated prevalence between 0.5% and 1%. The disease has gathered increased attention in the most recent years, leading to a better understanding of the disease’s pathophysiology and its implications and to the development of newer therapeutic strategies. A better, more integrated approach is already in use for other chronic inflammatory dermatological diseases such as psoriasis, for which metabolic comorbidities are well-established and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…This response can be explained by the fact that PGZ induces the accumulation of free fatty acids, as reported by Baranowski et al [ 51 ]. The recent evaluation of the metabolic comorbidities in vitiligo patients [ 10 ], together with the known presence of pro-inflammatory cytokines linked to insulin resistance [ 52 ], defends the hypothesis of considering metabolic derangements as a new target to improve the quality of life of vitiligo patients. Unfortunately, vitiligo remains a difficult disease to treat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This response can be explained by the fact that PGZ induces the accumulation of free fatty acids, as reported by Baranowski et al [ 51 ]. The recent evaluation of the metabolic comorbidities in vitiligo patients [ 10 ], together with the known presence of pro-inflammatory cytokines linked to insulin resistance [ 52 ], defends the hypothesis of considering metabolic derangements as a new target to improve the quality of life of vitiligo patients. Unfortunately, vitiligo remains a difficult disease to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our vitiligo unit carried out a retrospective analysis underlining that vitiligo patients frequently display modest alterations of the spectrum of the metabolic syndrome [ 10 ]. Specifically, while in vitiligo patients, lower levels of total cholesterol were measured overall, the distribution of lipid subpopulations was less favorable with respect to the healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, little attention has been paid to the role of environmental factors like diet or PE training or the level of habitual physical activity in vitiligo disease. In fact, to the best of our knowledge, there are no studies focused on PE or habitual physical activity level and vitiligo disease, although several studies with similar etiological factors have consistently identified significant associations between vitiligo (as well as its severity) with MetS ( Ataş and Gönül, 2017 ; Sharma et al, 2017 ; Tanacan and Atakan, 2020 ; Verma et al, 2021 ) or related dysfunctions such as higher blood plasma concentrations of low-density lipoprotein (LDL- cholesterol), low high-density lipoprotein (HDL-cholesterol), and insulin resistance ( Karadag et al, 2011 ; Azzazi et al, 2021 ; Demirbaş et al, 2021 ; D’Arino et al, 2021 ). It is well established that a mainly sedentary lifestyle behavior and poor nutritional patterns are the most important risk factors for the onset of MetS or cholesterol disorders ( Lira et al, 2010 ; Edwardson et al, 2012 ).…”
Section: Overview Of Vitiligo Developmentmentioning
confidence: 99%
“…Vitiligo is usually associated with different autoimmune disorders such as thyroid diseases, diabetes mellitus, lupus, inflammatory bowel disease, psoriasis and atopic dermatitis among others. [ 3 ] Other authors have observed also metabolic comorbidities[ 4 ] and psychological and psychiatric disorders. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%